Aspectos da biologia, caracterização foliar e manejo químico de Conyza bonariensis (L.) Cronquist (Asteraceae) e Conyza canadensis (L.) Cronquist (Asteraceae) - Inacio, Estela Maris (2012)
The genus Conyza includes approximately 60 species, which are distributed throughout most of the world. Globally the weed species Conyza canadensis and Conyza bonariensis infest more than 40 types of crops. Both species are noted for their ability to infest abandoned areas (vacant lots and roadsides), pastures, perennial crops (citrus and coffee) and annual crops (cotton, corn, soybeans and wheat). Knowledge of the biology of these weeds is required to inform management actions to control their spread for example to identify which is the best control strategy and time for action. We conducted experiments at the Center for Agricultural Sciences / UFSCar, between 2010 and 2011, to achieve 3 research objectives: (1) determine the germination behavior of C. canadensis and C. bonariensis under different environmental conditions [different temperatures (10oC, 15oC, 20oC, 25oC, 30oC and 35oC), light (with and without), sowing depth (0, 0.5, 1, 2, 3, 5, 7, and 10 cm) and germination in soils with different textures (sand, intermediate and clay)], (2) characterize the different types of leaf surface of C. bonariensis and C. canadensis by scanning electron microscopy, (3) determine the effects of the application of the herbicide glyphosate (0.42 kg a.i. ha-1), when mixed with ammonium glyphosate (0.5 kg a.i. ha-1), bentazon (0.72 kg a.i. ha-1), chlorimuron-ethyl (0.15 kg a.i. ha-1), carfentrazone-ethyl (0.03 kg a.i. ha-1), 2,4-D (1.0 L a.i. ha-1), metribuzin (0.48 kg a.i. ha-1) and sulfentrazone (0.6 kg ha-1), in addition to these herbicides applied in isolation. For both C. bonariensis and C. canadensis, the best seed germination and germination rate temperature was approximately 250C. Seed germination rate of both species was higher when exposed to light, compared with seeds germinated in the dark. Sowing depth and soil texture also influenced germination, with seeds of both species showing higher emergence rates in intermediate texture soils when they were sown on the soil surface (0 cm), whereas emergence rates declined at sowing depths ≥0.5 cm. Analysis of leaf surfaces revealed that both species are amphistomatic with stomata on the adaxial and abaxial leaf surfaces, that the non-glandular trichomes are unicellular and multicellular, and that C. bonariensis has a visually larger amount of trichomes on the adaxial surface. The most effective herbicide treatments for the chemical control of C. bonariensis were glyphosate + ammonium glyphosate, glyphosate + bentazon, glyphosate + chlorimuron - ethyl and glyphosate + metribuzin, whereas for C. canadensis, the best treatments were mixtures of glyphosate + ammonium glyphosate, glyphosate + bentazon and glyphosate + metribuzin.